Empirical analysis of heat transfer and friction factor of water/graphene oxide nanofluid flow in turbulent regime through an isothermal pipe. (5th November 2017) - Ranjbarzadeh, Ramin; Karimipour, Arash; Afrand, Masoud; Isfahani, Amir Homayoon Meghdadi; Shirneshan, Alireza
Highlights: Investigation of water/graphene oxide nanofluid heat transfer and friction factor. Develop the experimental circular copper tube setup to include turbulent flow. 28% increase of thermal conductivity compared with the base fluid. 36.5% increase in convection coefficient compared with base fluid. Present nanofluid can be used in coolant systems like air heat exchangers. Abstract: Nanofluid flow is considered one of the most important solutions for improving heat transfer systems. In this study, an isotherm heat transfer system has been designed and built in order to investigate the effect of utilizing water/graphene oxide nanofluid flow on heat transfer and the friction coefficient in a circular profile copper tube. The range of nanofluid concentration is considered as 0%, 0.025%, 0.05%, 0.075%, and 0.1% of volume fraction and Reynolds number of the turbulent flow is chosen between 5250 and 36, 500. The nanofluid is made through a two-step method. The absolute value of Zeta potential equals 41 mV, which is measured experimentally and shows acceptable stability. The thermal conductivity of nanofluid has a maximum of 28% increase in comparison to the base fluid. Considering the experiential data from this study, the Nusselt number, the convective heat transfer coefficient, the pressure loss, the friction factor, and the coefficient of performance are investigated. In order to achieve validation, the results of this study are compared with former studies. Maximally, the nanofluid has a 40.3% augmentation in the convective heat transfer coefficient in comparison to the base fluid. In addition, a minor augmentation takes place during pressure loss and friction coefficient by utilizing the nanofluid that reaches a maximum of 16%. However, the thermal performance coefficient maximally increases by 1.148. According to the achieved results, the present nanofluid can be used in coolant systems like air cooling heat exchangers.